Efeitos da cafeína e do diclofenaco sobre o estresse oxidativo e a inflamação em ratos submetidos ao exercício físico - Barcelos, Rômulo Pillon (2015)
Exercise can represent a physical stress that disrupts the homeostasis. Elevated muscle oxygen consumption increases reactive oxygen species (ROS) and inflammatory proteins production, leading to oxidative stress and systemic inflammation. Nowadays, both caffeine, a commonly compound present in many commercial beverages and medicines, and the non-steroidalanti-inflammatory drugs (NSAIDs), including diclofenac, have been used in sports competitions events. Considering that athletes intent to improve their sports performance, mainly on high intensity competitions and short duration that can lead to inflammation and pain, a great number of athletes consume caffeine and NSAIDs due they ergogenic effects or avoid inflammation and loss of performance. However, little is known about the physical exercise and concomitant use of caffeine/diclofenac. Considering the sport specificity, most authors have focused exercise in skeletal muscle studies. In view of the important role of liver during physical activities, one of the goals of this work was to analyze the effect of caffeine and diclofenac on cell damage, hepatic inflammation and oxidative stress markers in exercised rats. In two papers, we highlight the effect of caffeine on the oxidative damage, inflammation and tissue adaptation in liver, muscle and plasma of training rats. The experimental protocol included four groups: sedentary-saline, sedentary-diclofenac, exercise-saline, and exercise-diclofenac. The exercised groups performed a 4-week aerobic swimming training protocol and were treated with saline or caffeine (6 mg/kg). We found significant changes on citrate synthase (CS), superoxide desmutase (SOD), glutathione peroxidase (GPx) and acetylcholinesterase (AChE) enzyme activities and aspartate aminotransferase (AST) and thiobarbituric acid reactive substances (TBARS) levels after training. These modifications were reverted by caffeine treatment. In the manuscript, we highlight the effects of diclofenac (10 mg/kg) on the inflammation induced by an acute exercise. Rats were divided in 4 groups: control-saline (CS), control-diclofenac (CD), exercise-saline (ES) and exercise-diclofenac (ED). The animals from the C and E groups received saline, while the groups CD and ED received diclofenac treatment during seven days previous to the exercise bout, which consisted in an acute bout of eccentric exercise lasting 90 min. We identified an increase in both gene expression and levels of proteins TLR4, MyD88, TRIF, NFκB, p65, IL-6, TNF-α and iNOS in the exercised groups. Diclofenac treatment blunted these responses exercised-induced. Taken together, the data indicate that diclofenac and caffeine interfere on oxidative and inflammation responses induced by physical exercise, altering the adaptive mechanisms of tissues under exercise.